Liquid biopsy-based clinical research in early breast cancer: The EORTC 90091-10093 Treat CTC trial. (August 2016) - Ignatiadis, Michail; Rack, Brigitte; Rothé, Francoise; Riethdorf, Sabine; Decraene, Charles; Bonnefoi, Hervé; Dittrich, Christian; Messina, Carlo; Beauvois, Melanie; Trapp, Elisabeth; Goulioti, Theodora; Tryfonidis, Konstantinos; et al.
Abstract: There is increasing evidence that breast cancer evolves over time under the selection pressure of systemic treatment. Today, treatment decisions in early breast cancer are based on primary tumour characteristics without considering the disease evolution. Chemoresistant micrometastatic disease is poorly characterised and thus it is not used in current clinical practice as a tool to personalise treatment approaches. The detection of chemoresistant circulating tumour cells (CTCs) has been shown to be associated with worse prognosis in early breast cancer. The ongoing Treat CTC trial is the first international, liquid biopsy-based trial evaluating the concept of targeting chemoresistant minimal residual disease: detection of CTCs following adjuvant chemotherapy (adjuvant cohort) or neoadjuvant chemotherapy in patients who did not achieve pathological complete response (neoadjuvant cohort). This article presents the rational and design of this trial and the results of the pilot phase after 350 patients have been screened and provides insights that might provide information for future trials using the liquid biopsy approach as a tool towards precision medicine (NCT01548677 ). Highlights: This study evaluates the concept of targeting minimal residual disease (presence of circulating tumour cells). Liquid-based biopsy clinical research is feasible. This is the first study of its kind in adjuvant therapy of breast cancer.